Visiones del dispositivo penal juvenil en la provincia de Santa Fe. Un recorrido por el Programa Libertad Asistida - Puyol, María Victoria (Universidad Nacional del Litoral, 2019)
This work aims to present visions of the juvenile penal dispositive through the perspective of the executive operators of the Assisted Liberty Program.Over recent decades, in Argentina, there have been a series of normative changes aimed at transforming the way in which childhood and adolescence are defined as well as the ways of organizing and regulating the government agencies involved on them. This article intends to investigate the way inwhich these normative changes imThis work aims to present visions of the juvenile penal dispositive through the perspective of the executive operators of the Assisted Liberty Program. Over recent decades, in Argentina, there have been a series of normative changes aimed at transforming the way in which childhood and adolescence are defined as well as the ways of organizing and regulating the government agencies involved on them. This article intends to investigate the way in which these normative changes impacted the executive segment of the juvenile penal dispositive in the province of Santa Fe, Argentina.From the voices of the executive operators ofthe Assisted Liberty Program, we reconstructtheir positions and representations around thecrystallized elements of the juvenile penal dis-positive.pacted theexecutive segment of the juvenile penal dis-positive in the province of Santa Fe, Argentina.From the voices of the executive operators ofthe Assisted Liberty Program, we reconstructtheir positions and representations around thecrystallized elements of the juvenile penal dis-positive.